A STRATEGIC MODEL FOR MEASURING INTELLECTUAL CAPITAL IN SERBIAN INDUSTRIAL ENTERPRISES - Kontić, Ljiljana; Čabrilo, Slađana (Economic Annals, 2009)
Measuring intellectual capital contributes to organisational success and brings managerial, cultural and organisational changes. In analysing the relevant literature on intellectual capital (IC), it emerges that the benefits of IC measuring and reporting have been linked to value creation. In order to provide a deeper understanding of the character and role of IC and adequate IC indicators, the main aim of this study is to propose a strategic model for measuring intellectual capital in Serbian industrial enterprises. The research findings revealed a lack of both employee innovativeness and permanent competence development of top managers and employees, which may be a significant problem in the potential growth of Serbian industry. The factor analysis showed that the proposed questionnaire (based on relevant scorecard methods) is adequate for investigating the phenomena of intellectual capital in industrial enterprises in Serbia.